COMBINING ABILITY ANALYSIS IN ORYZA SATIVA L. (Biological Sciences - PJSIR, 2022)
A diallel cross involving four rice cultivars; Basmati 370, Basmati 385,4048 and Basmati 198 was studied in theF I generation for anther length, IOO-anther weight, pollen grain size and percent filled spikelets. Both general combiningability (OCA) and specific combining ability (SCA) were significant for all traits except pollen grain size. The OCAmean square magnitude was considerably higher than SCA mean square for anther length and I OO-anther weight. Theinverse was found for percent filled spikelets. It reveals additive gene effects for anther length, IOO-anther weight anddominance gene effects for percent filled spikelets. Basmati 198 displayed positive and significant general combiningability effects for anther length and IOO-anther weight. Basmati 370 was the best general combiner for percent filledspikelets. 4048 x Basmati 198, Basmati 370 x 4048 and Basmati 370 x Basmati 385 were the best specific combinersfor anther length, 100-anther weight and percent filled spikelets respectively and are expected to contribute higherfrequency of desirable plants than other crosses in subsequent generations.